2005
DOI: 10.1002/sia.1949
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal electron emission from MgO thin film under ion irradiation

Abstract: Energy distributions of secondary electrons from an MgO thin-film surface under ion irradiation were investigated. The abnormal ion-induced secondary electron emission was observed in addition to the normal emission. The abnormal emission observed in the present study is found to be a kind of selfsustained emission because it continued after stopping ion irradiation. The energies of the abnormal secondary electrons are lower than the vacuum level at the MgO surface by ∼7-10 eV and its energy distribution is cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Therefore, γ is one of the most important parameters of the MgO protective layer for improving the discharge characteristics, 1,6 and the IISE phenomenon in MgO films has been intensively studied. [7][8][9][10][11][12][13][14][15] The magnitude of γ is strongly influenced by the MgO film electronic structure. It has been reported that γ is closely related to defect states 16 and γ increases as the number of surface defect states in MgO increases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, γ is one of the most important parameters of the MgO protective layer for improving the discharge characteristics, 1,6 and the IISE phenomenon in MgO films has been intensively studied. [7][8][9][10][11][12][13][14][15] The magnitude of γ is strongly influenced by the MgO film electronic structure. It has been reported that γ is closely related to defect states 16 and γ increases as the number of surface defect states in MgO increases.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in the firing voltage can be realized by increasing  [1]. Therefore, the extensive studies on the IISE from the protective layer have been performed [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have been involved in the study of the effects of charging on the electron emission from insulator film surfaces. [13][14][15][16][17][18][19] In the previous study, we investigated the effects of the amount and polarity of wall charge on t s and found that a positive wall charge on the MgO surface of the cathode side is advantageous in improving the response of the discharge. 19) In this study, we investigated the effects of wall charge on the property of exoelectron emission in AC-PDPs, in particular, the accumulation and decay of exoelectron sources, by measuring the discharge characteristics, i.e., the statistical delay time, t s , using a specially designed test panel.…”
Section: Introductionmentioning
confidence: 99%